2019
DOI: 10.3892/ol.2019.10888
|View full text |Cite
|
Sign up to set email alerts
|

POPDC3 is a potential biomarker for prognosis and radioresistance in patients with head and neck squamous cell carcinoma

Abstract: Radiotherapy is the primary means of treatment for patients with head and neck squamous cell carcinoma (HNSCC); however, radioresistance-induced recurrence is the primary cause of HNSCC treatment failure. Therefore, identifying specific predictive biomarkers of the response to radiotherapy may improve prognosis. In the present study, to identify the potential candidate genes associated with radioresistance in patients with HNSCC, the microarray datasets GSE9716, GSE61772 and GSE20549 were downloaded from the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Subsequent rapid expansion of the ISC population was also observed, leading to the conclusion that POPDC1 down-regulation and ensuing stem cell proliferation, in response to radiation therapy may be an underlying cause of resistance to radiotherapy treatment. The same phenomenon has also been observed as a result of POPDC3 down-regulation in other cancers such as HNSCC, lung cancer, and oesophageal cancer (Table 1) (He et al, 2019).…”
Section: Emt and Differentiationsupporting
confidence: 75%
See 1 more Smart Citation
“…Subsequent rapid expansion of the ISC population was also observed, leading to the conclusion that POPDC1 down-regulation and ensuing stem cell proliferation, in response to radiation therapy may be an underlying cause of resistance to radiotherapy treatment. The same phenomenon has also been observed as a result of POPDC3 down-regulation in other cancers such as HNSCC, lung cancer, and oesophageal cancer (Table 1) (He et al, 2019).…”
Section: Emt and Differentiationsupporting
confidence: 75%
“…The extent of POPDC1 glycosylation in cancer cells and the functional relevance of this has yet to be investigated. This extracellular sequence is followed by three transmembrane domains and a larger, intracellular carboxy-terminal domain (CTD) Kim et al, 2010;Luo et al, 2012 Oesophageal and lung cancer -Overexpression of POPDC3 correlates with greater radiotherapy resistance He et al, 2019 Note: Expression of POPDC2 and POPDC3 varies between tissue type and across various cancer types. Dysregulation of POPDC2 is mainly observed in cardiovascular disease and breast cancer.…”
mentioning
confidence: 99%
“…High expression was related to tumor category, lymphatic metastasis and pathological stage. Xu He et al [21] downloaded the GSE9716, GSE61772 and GSE20549 from the Gene Expression Omnibus (GEO) database and reported that high POPDC3 expression associated with poor a prognosis for patients with HNSCC. But these genes cannot accurately predict patient survival because a single gene is modulated by many factors.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 presents a summary of clinicopathological features in the final TCGA-SKCM cohort. Further, the final dataset was normalized by quantile normalization method, which has been extensively used in the past for similar studies [34,35,36].…”
Section: Dataset and Pre-processingmentioning
confidence: 99%